Paternal involvement and dyadic affective flexibility in parent-child coregulation - Cunningham, Mark R., author; Lunkenheimer, Erika, advisor; Lucas-Thompson, Rachel, committee member; Yan, Ruoh-Nan, committee member (Colorado State University. Libraries, 2017)
The present study examined the role of paternal involvement in parent-child positive affect and dyadic flexibility. Previous research has shown that father's involvement may provide contextual support that may protect dyadic subsystems from stressors and promote positive parenting practices within the family unit. Additionally, involved fathers develop more sensitive relationships with their children. Thus, it was hypothesized that parent-child dyads with greater paternal involvement would show greater positive affect and dyadic flexibility, which has been shown to result in children's decreased externalizing problems. Mother-child (n = 209) and father-child dyads (n = 88) interacted in a block design task at home when children were 3 years old. Dynamic systems-based methods were used to derive dyadic positive affect and dyadic flexibility from observational coding. Mother's self-report was used to determine paternal involvement in comparison to all potential caregivers. The results of this study did not show a relation between paternal involvement and dyadic positive affect and flexibility. Implications of these findings are discussed and provide new directions for research into parent-child coregulation dynamics.